PELAKSANAAN URAIAN TUGAS OPERATOR SEKOLAH DI SLTA SE-KABUPATEN PASAMAN DAN KABUPATEN PASAMAN BARAT - Windi Lestari; Rusdinal Rusdinal; Irsyad Irsyad; Tia Ayu Ningrum (Jurnal Manajemen Pendidikan, 2026)
Good school governance requires an administrative system capable of supporting the entire process of planning, implementation, control, and evaluation of educational programs.This study aims to examine the implementation of school operator job descriptions in senior high schools throughout Pasaman and West Pasaman Regencies. This study employs a quantitative approach using a descriptive method. The study sample consisted of 91 school operators selected using simple random sampling. Data were collected using a Semantic Differential scale questionnaire that had passed validity and reliability tests, then analyzed using the mean, standard deviation, and Respondent Achievement Level (RAL). The results indicate that the implementation of school operator job descriptions falls into the “good” category with a mean score of 4.43. The working conditions indicator received the highest RAC of 88.62%, followed by responsibility at 88.48% and authority at 88.42%, all of which fell into the “good” category. This study provides an empirical overview of the implementation of school operator job descriptions based on the aspects of responsibility, working conditions, and authority at the senior high school level in two regencies that have rarely been specifically studied.